Calcium arrhythmogenicity of Purkinje fibers: importance of the animal model - Stuyvers, Bruno D. (Frontiers in Physiology, 2025)
Ventricular tachycardias (VTs) and fibrillations (VFs) are frequent complications of ischemic myocardial infarction (MI). Because their initiation mechanism remains unknown, these arrhythmias are virtually unpredictable and often degenerate into cardiac arrest and syncope without immediate medical assistance. Electrical mapping and ablation techniques have located the origin of ischemic arrhythmias in the terminal arborizations of the cardiac conduction system, the Purkinje fibers. A classical model of MI in the dog has demonstrated that abnormal calcium (Ca2+) cycling in the Purkinje cells (Pcells) is the source of non-driven depolarizations (DADs) in the conduction tissue and is likely to create the pro-arrhythmic conditions of human ischemic heart. A better understanding of Ca2+ abnormalities in Pcells post infarction is an evident prerequisite for elucidating the mechanism of ischemic arrhythmias. Nevertheless, a unique Ca2+ handling system was discovered in Pcells, exhibiting fundamental differences compared with the well-known model of Excitation-Contraction coupling of ventricular cardiomyocytes. This cellular specificity of Purkinje fibers was observed in large mammalian species but not in murine hearts, where Purkinje cells are comparable to ventricular myocytes and designed to respond to 400–600 stimulations/min. The present report reviews the mechanism of Ca2+ arrhythmogenicity in Pcells of large mammalian hearts and documents the need for animal models that simulate the size and function of human hearts to study ischemic arrhythmias.